TRADE UNIONS’ COLLECTIVE POWER IN DECARBONIZATION FOR ENSURING A JUST ENERGY TRANSITION SYSTEMATIC REVIEW - Sulistyo, Eko; Karsidi, Ravik; Kartono, Drajat Tri; Arif, Akbarudin (Journal of Social Politics and Governance (JSPG), 2025)
A just energy transition requires not only technological shifts toward clean energy but also social inclusion and fairness in the world of work. Trade unions play a dual role—protecting workers while shaping energy policy and advancing social justice—yet their strategic contributions remain understudied, especially in comparisons between developed and developing countries. This study conducts a Systematic Literature Review (SLR) using the PRISMA protocol on 25 peer-reviewed publications (2015–2025). Trade union strategies are interpreted using Kalt’s (2022) typology—oppositional, reactive, affirmative, transformational—and analyzed through six empowerment dimensions: structural, organizational, advocacy/negotiation, socio-cultural, economic, and ideological. Findings show unions in developed countries predominantly adopt affirmative and transformational strategies, engaging in reskilling initiatives, climate negotiations, and institutionalized social dialogue. Conversely, unions in developing countries rely more on oppositional or reactive strategies due to limited institutional capacity and weaker bargaining positions amid rapid transition policies. The study underscores the need for multidimensional empowerment to strengthen unions’ ability to influence policy and safeguard workers during decarbonization. These insights offer practical implications for policymakers and labor organizations committed to equity, sustainability, and socio-ecological justice in energy transitions.